2018
DOI: 10.4103/ijo.ijo_486_17
|View full text |Cite
|
Sign up to set email alerts
|

WINROP algorithm for prediction of sight threatening retinopathy of prematurity: Initial experience in Indian preterm infants

Abstract: Purpose:To determine the efficacy of the online monitoring tool, WINROP (https://winrop.com/) in detecting sight-threatening type 1 retinopathy of prematurity (ROP) in Indian preterm infants.Methods:Birth weight, gestational age, and weekly weight measurements of seventy preterm infants (<32 weeks gestation) born between June 2014 and August 2016 were entered into WINROP algorithm. Based on weekly weight gain, WINROP algorithm signaled an alarm to indicate that the infant is at risk for sight-threatening Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
1
20
3
2
Order By: Relevance
“…This is what distinguishes our study from those conducted in other developing countries that showed lower sensitivity ranging from 80 to 90%. 12 , 14 - 16 , 20 , 24 - 27 Sensitivity has also been demonstrated to be lower in heavier infants (>1000 grams) in developed countries, which was not the case in our series. 14 …”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This is what distinguishes our study from those conducted in other developing countries that showed lower sensitivity ranging from 80 to 90%. 12 , 14 - 16 , 20 , 24 - 27 Sensitivity has also been demonstrated to be lower in heavier infants (>1000 grams) in developed countries, which was not the case in our series. 14 …”
Section: Discussioncontrasting
confidence: 71%
“…Large variations in WINROP specificity have been reported in cross-sectional studies that validated the WINROP. 8 , 10 - 12 , 14 Variability in cases, neonatal care, survival rates, and screening practices could all account for those discrepancies. However, since preventing retinal detachment and, ultimately, blindness is the goal of ROP screening, the sensitivity and NPV of ROP screening examinations are thought to be more relevant than its specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 summarizes the results of 12 countries of both high-and moderate-/low-income status who have participated in the WINROP study, including our study. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Overall, WINROP has been reported to have good efficacy as a screening tool. However, the sensitivity of WINROP varies among countries.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In Asia, it has been reported in China, Korea, Taiwan, India and Japan. 6,7,11,15,16 Based on a PubMed search, no similar reports are available from the South East Asia region, especially in a developing country. This study thus aims to investigate the efficacy of WINROP in the East Coast of Malaysia.…”
Section: Introductionmentioning
confidence: 99%